2012
DOI: 10.1177/1359105311429203
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of coping strategies, social support, and attachment style with posttraumatic growth in cancer survivors

Abstract: This cross-sectional study investigated attachment style, coping strategies, social support, and posttraumatic growth (PTG) in 54 cancer survivors. Secure attachment was significantly associated with active coping, positive reframing, and religion, and these were all associated with PTG. Insecure types of attachment and social support variables were unrelated to PTG. Regression analysis suggests that positive reframing and religion as coping strategies may mediate the relationship between secure attachment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
80
2
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 19 publications
12
80
2
9
Order By: Relevance
“…43 Researchers also suggested that health care providers might help the recovery of patients by facilitating posttraumatic growth. 44,45 In our sample, the illness perceptions were associated with rejection episodes and lower graft functioning. When individuals develop a physical disease, they tend to generate a specific pattern of beliefs and opinions (mental representations) that have the main role of helping them to understand their illness.…”
mentioning
confidence: 92%
“…43 Researchers also suggested that health care providers might help the recovery of patients by facilitating posttraumatic growth. 44,45 In our sample, the illness perceptions were associated with rejection episodes and lower graft functioning. When individuals develop a physical disease, they tend to generate a specific pattern of beliefs and opinions (mental representations) that have the main role of helping them to understand their illness.…”
mentioning
confidence: 92%
“…Strong fear of rejection assumes hyper-activation of the mechanisms detecting such a threat, and this pattern is probably generalized into a more sensitive perception of other types of threat as well, such as the illness. Secure attachment is regarded as a protective factor mitigating the effect of stress in cancer and preventing trauma (Cicero et al, 2009;Schmidt, Blank, Bellizzi, & Park, 2012). Thus evaluating the fear of rejection can detect persons at greater risk of emotional distress when they are going through cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Por eso, la calidad del vínculo establecido entre la persona enferma y sus cuidadores debe de ser particularmente relevante para su bienestar emocional. En esta línea, la investigación más reciente apunta a que el estilo de apego seguro contribuye a una mejor adaptación a las dificultades que conlleva el cáncer (Cicero, Lo Coco, Gullo y Lo Verso, 2009;Hunter, Davis y Tunstall, 2006;Lo et al, 2010;Schmidt, Blank, Bellizzi y Park, 2012). Muy recientemente se ha puesto de relieve la importancia del estilo de apego y del ajuste de la pareja cuidadora en cáncer de colon (Hall, Armstrong, Cabral y Kim, 2012) y pulmón (Porter et al, 2012).…”
Section: Introductionunclassified